United States Department of Justice Application for Certification of Identification - United States. Department of Justice; Bredig, Georg (1942)
Georg Bredig's (1868-1944) completed application for a United States certificate of identification. Document contains identifying information about Bredig, and a written statement with his reason for leaving Germany. Bredig has written in the top left corner, "My certificate of Identification. Febr. 18. 1942. No. 39036. Copy"
Keywords: Bredig, Georg, 1868-1944; Emigration and immigration; United States. Department of Justice; Citizenship